Factors associated with HIV testing among young men who have sex with men in Myanmar: a cross‐sectional study. Issue 3 (6th November 2017) - Pham, Minh D; Aung, Poe Poe; Paing, Aye Kyawt; Pasricha, Naanki; Agius, Paul A; Tun, Waimar; Bajracharya, Ashish; Luchters, Stanley
Abstract: Introduction: In Myanmar, men who have sex with men (MSM) experience high risk of HIV infection. However, access to HIV testing and prevention services remains a challenge among this marginalized population. The objective of this study was to estimate population prevalence and correlates of prior HIV testing among young MSM (YMSM) and informs the development of HIV testing and intervention programmes that respond to the specific needs of this population. Methods: Five hundred and eighty‐five YMSM aged 18 to 24 years were recruited using respondent‐driven sampling (RDS) in a cross‐sectional survey conducted in six townships of Myanmar. RDS‐adjusted population estimates were calculated to estimate prevalence of HIV testing; RDS‐weighted logistic regression was used to examine correlates of HIV testing in the past 6 months and in a lifetime. Results: There were 12 participants who reported receiving a HIV‐positive test; of those, five were tested in the past 6 months. The RDS‐weighted prevalence estimates of lifetime (any prior) HIV testing was 60.6% (95% CI: 53.3% to 66.4%) and of recent (≤ 6 months) HIV testing was 50.1% (95% CI: 44.1% to 55.5%). In multivariable analysis, sexual identity was associated with lifetime but not recent HIV testing. Lifetime and recent HIV testing were associated with having three or more male sexual partners in the past 12 months (adjusted ORs (aORs) = 2.28, 95% CIs: 1.21 to 4.32 and 2.69, 95% CI: 1.59 to 4.56), having good HIV‐related knowledge (aORs = 1.96, 95% CIs: 1.11 to 3.44 and 1.77, 95% CI: 1.08 to 2.89), reporting high HIV testing self‐efficacy (aORs = 13.5, 95% CIs: 6.0 to 30.1 and 9.81, 95% CI: 4.27 to 22.6) and having access to and use of non‐HIV health‐related services in the past 12 months (aORs = 13.2, 95% CIs: 6.85 to 25.6 and 7.15, 95% CI: 4.08 to 12.5) respectively. Conclusions: HIV testing coverage among YMSM aged 18 to 24 years old in Myanmar is still suboptimal. Integrated HIV testing and prevention services in existing health service provision systems with tailored HIV information and education programmes targeting YMSM to improve HIV‐related knowledge and self‐efficacy may help to promote regular HIV testing behaviour and contribute to sustainable control of the HIV epidemic among this marginalized population in Myanmar.